2010
DOI: 10.4314/naj.v40i1-2.55554
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of factors driving the adoption of yam minisett technology by farmers in Abia State, Nigeria.

Abstract: Yam () is an important tuber crop in Nigeria, where it is produced mainly as a source of food crop especially carbohydrate. The current annual production is estimated at 26.587 million metric tons (FAO, 2005). In 1997 alone, Nigeria accounted for 75% of the world production (Manyong 2001. Although yam production in Nigeria is quite high there is still need for increased production to satisfy domestic and possibly export demand (Asumugha 2004). However, production of yam is highly expensive when compared with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Results also indicated that the major problems hindering the adoption of yam minisett technology included scarcity of treatment chemicals, scarcity of mother seed yam and inability to understand the highly technical procedure, others included tediousness of the practice, lack of substantial increase in harvest, small size of tubers, and poor compatibility to farming system (Table 5). In comparison, Anyaegbunam et al (2009) found that major problems hindering adoption of improved technologies were high cost of input, unavailability of credit, inadequate access to land and insufficient extension services.…”
Section: Determinants Of Yam Minisett Technology Adoptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results also indicated that the major problems hindering the adoption of yam minisett technology included scarcity of treatment chemicals, scarcity of mother seed yam and inability to understand the highly technical procedure, others included tediousness of the practice, lack of substantial increase in harvest, small size of tubers, and poor compatibility to farming system (Table 5). In comparison, Anyaegbunam et al (2009) found that major problems hindering adoption of improved technologies were high cost of input, unavailability of credit, inadequate access to land and insufficient extension services.…”
Section: Determinants Of Yam Minisett Technology Adoptionmentioning
confidence: 99%
“…About 89 percent of the farmers were married, with modal family size between 4 and 6; indicating the presence of substantial intra-household demand for yam for food and income security, as well as availability of family labour as an input for yam production. High cost of labour was found to be a major constraint to adoption of yam minisett technology in Abia State of Nigeria (Anyaegbunam et al, 2009). Therefore, the availability of substantial family labour may reduce the cost of labour, thereby increasing the chances of the adoption of yam minisett technology in the study area.…”
Section: Socio-economic Characteristics Of Yam Farmersmentioning
confidence: 99%
“…Oladele (2005) reported that the propensity to adopt improved beans and maize varieties in Southern Nigeria was influenced by extension visit. Supporting this finding, Anyaegbunam, Eze, Ogbonna, and Korieocha (2009) found that major problems hindering adoption of improved technologies were high cost of input, unavailability of credit, inadequate access to land and insufficient extension services.…”
Section: Reasons For Non-adoption Of Improved Oil Palm Fruit Processimentioning
confidence: 80%
“…Similarly, Ajieh (2012) found that farmers had a moderate awareness of the minisett technology in Delta State. Insufficient extension services have been implicated in the low adoption rate of YMT in Nigeria (Anyaegbunam et al 2009;Okoro, 2008). Broadly speaking, the rate of extension contact and adoption differs in years and in all the regions of the country (Table 2).…”
Section: Informational Factorsmentioning
confidence: 99%
“…Labour alone can account for 78.1% of the production cost and, most YMT adopters use hired labour which is expensive and sometimes unreliable (Eyitayo, 2010). The high cost of labour was found to be a major constraint to the adoption of the YMT in Abia State of Nigeria (Anyaegbunam et al 2009). Without credit facilities, high costs of labour and farm inputs immensely contribute to the expenses in YMT thereby making it to be financially demanding for smallholder farmers to adopt.…”
Section: Economic Factorsmentioning
confidence: 99%